Hábitos alimentares de jovens de tubarão-martelo Sphyrna lewini (Griffith & Smith, 1834) (Chondrichthyes, Sphyrnidae) no litoral do estado de São Paulo - Dolphine, Priscila Marchetti [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The feeding habits of the neonats and juvenils hammerhead shark, Sphyrna lewini, landed at coast of the state São Paulo, southern Brazil, were analyzed concerning the diet composition, seasonal and sexual variations, ontogenetic diet shifts, niche overlap and niche breadth. Fishery data and biological samples were obtained from the artisanal fishery fleet. The sharks were caught by gillnet with fishing boats operating from 2 to 12 nautical miles from the shore and depths from 6 to 20 m. Stomach content analyses included Numerical Percent (%N), Occurrence Frequency (%FO), Mass Percent (%M) and Index of Relative Importance (%IRI). From May2012 to May 2014253S. lewini specimens were sampled. The stomach contents analysis was made in248individuals. About 84% of the analyzed sharks had items in the stomach. 16 items were identified, 11 at species level, three at genus level, and two as families. The prey category fishes was the most important in the diet, corresponding to 57 %IRI, while crustaceans (25 %IRI) and cephalopods (18 %IRI) were complementary items. The identified families were: Fishes -Ariidae, Engraulidae, Ophichtidae Sciaenidae and Trichiuridae; Cephalopods - Loliginidae; and Crustaceans - Penaeidae and Sergestidae. The diet of this species presented, mainly, seasonal and ontogentic variations. A high level of feeding overlap between males and females, and neonates and juveniles; however such overlap was smaller for the latter categories. The diversity of prey species in the diet was low, mainly for males and juveniles.Sphyrna lewini neonates and juveniles have predominantly ictiophagous feeding habits, completing the diet with crustaceans and cephalopods

Os hábitos alimentares de neonatos e jovens de tubarões-martelo, Sphyrna lewini, desembarcados no litoral do estado de São Paulo, foram analisados quanto a composição da dieta, variações sazonais, ontogenéticas e sexuais, sobreposição alimentar e amplitude de nicho. Os exemplares foram capturados com redes de emalhe, por embarcações operando a uma distância da costa entre duas a 12 milhas náuticas, em profundidades variando de seis a 20 metros.Para as análises foram utilizados os dados de Porcentagem Numérica (%N), Freqüência de Ocorrência (%FO), Porcentagem de Massa (%M) e Índice de Importância Relativa (%IRI). Entre maio de 2012 e maio de 2014 foram amostrados 253 exemplares de S. lewini. A análise do conteúdo estomacal foi realizada em 248 espécimes. Desse total, 84% apresentaram algum tipo de alimento. Foram identificados16 itens, sendo 11identificados em nível de espécie, três como gênero e dois como família. A categoria peixes foi a mais representativa,correspondendo a 57 %IRI, seguida por crustáceos (25 %IRI) e cefalópodes (18%IRI). As famílias observadas na dieta foram: Peixes:Ariidae, Engraulidae, Ophichtidae Sciaenidae e Trichiuridae; Cefalópodes: Loliginidae; e Crustáceos: Penaeidae e Sergestidae. A dieta da espécie apresentou, principalmente, diferenças sazonais e ontogenéticaS.Foi observada uma alta sobreposição na alimentação entre machos e fêmeas, e neonatos e jovens, porém esse valor foi menor entre estas últimas categorias.A diversidade da dieta apresentou-se baixa, principalmente nos machos e jovens.Neonatos e jovens de Sphyrna lewini são predominantemente ictiófagos, alimentando-se, secundariamente, de crustáceos e cefalópodes
Keywords: Fishes; Peixe; Nutrição; Elasmobrânquios; São Paulo (SP)